Developing Students' Information Technology (IT) Utilization Skills And Students Collaboration With Google Sites - Dania Suryantari; Rahmat Mulyono (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
The direction of education policy today is manifested in the implementation of the independent curriculum. In the independent curriculum, teachers are given the freedom to apply learning methods, classroom management, selection of essential materials according to student's needs, and appropriate types of evaluation. Teachers should conduct an initial diagnostic of learning, and understand the learning achievements according to the learning stage, character, as well as the interests and talents of the students. The purpose of this study is to determine whether the implementation of blended learning methods using a Learning Management Systems (LMS) in the form of Google sites can develop information technology (IT) utilization skills and collaboration among students. The research subjects were students in class 7A of the odd semester of the academic year 2022/2023. The research instrument was a questionnaire filled out online using Google forms. The questionnaire questions were divided into two categories, related to the use of Google sites to develop skills and attitudes of collaboration among students in creating a website. The results of the questionnaire analysis showed that the students felt that creating content on the website using Google sites was easy and interesting, and it could develop their skills in utilizing information technology that is integrated into Google Workspace for Education. The students' collaborative attitudes were also formed through task allocation and discussions in determining website design ideas. It can be concluded that the use of Google sites can develop information technology utilization skills and collaboration among students.